Social pressure for religious conformity and anti-gay sentiment among Muslim and Christian youth. Issue 2 (7th February 2020) - Van Droogenbroeck, Filip; Spruyt, Bram
Abstract: Research on civic education, for the most part, investigates the alleged outcomes of deliberate civic education programs. Remarkably, few types of research have investigated how the outcomes of group process (e.g. based on religion) in schools, and more specifically, the pressure to conform to in-group norms, relate to civic educational goals (e.g. promoting tolerance for Lesbian, Gay, Bisexual, Transgender people). Against that background, this paper has two objectives. First, we assess social variation in perceived social pressure for religious conformity among Christian and Muslim Youth enrolled in secondary education in Flanders ( N  = 2765). Second, we investigate the relationship between perceived social pressure for religious conformity and anti-gay sentiment. Our analyses are guided by social identity theory and rely on multilevel analysis. We find that for both Christian and Muslim youth, anti-gay sentiment is higher among young people who experience higher social pressure through the perceived expectations from talking with significant others about religion.